2023
DOI: 10.3389/fmars.2022.1073264
|View full text |Cite
|
Sign up to set email alerts
|

Mucus-associated microbiotas among different body sites of wild tuna from the South China Sea

Abstract: The mucus-associated symbionts have profound impacts on the pathogen defense, metabolism, and development of aquatic animals. To understand the microbial structure of regional endothermic fish, a total of 52 samples from the skin, oral, gill, and hindgut of wild tuna Thunnus albacares and T. obesus were determined by 16S amplicon sequencing. The results showed the diversity and composition of microbial communities varied in the four different body sites of tunas, with a greater heterogeneity between the extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Microbiotas in the mucosal layer are appointed to represent resident bacteria ( Kashinskaya et al, 2017 ), and they showed more microbial diversity in adults than in juveniles. However, no difference was found in gut content microbial diversity and composition between juvenile and adult tunas, which was similar to our previous study in Zou et al (2023) . It is recognized that host-associated factors, such as diet, age, and species, are important factors influencing gut microbial diversity and composition ( Ou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Microbiotas in the mucosal layer are appointed to represent resident bacteria ( Kashinskaya et al, 2017 ), and they showed more microbial diversity in adults than in juveniles. However, no difference was found in gut content microbial diversity and composition between juvenile and adult tunas, which was similar to our previous study in Zou et al (2023) . It is recognized that host-associated factors, such as diet, age, and species, are important factors influencing gut microbial diversity and composition ( Ou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…For tuna, a set of specialized gut bacteria may evolve specific interactions with the host. Acinetobacter , for instance, is one of the most abundant gut bacteria of tunas ( Minich et al, 2020 ; Zou et al, 2023 ), and it was significantly different in the proportion of relative abundance between adult and juvenile tunas ( Figure 1 ). This study detected a different gut mucosal microbial structure between juveniles and adults, and similar size-specific taxa differences were found in both yellowfin tuna and bigeye tuna, as described in Gadoin et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al 2023), and has likewise been reported in the skin of farmed Thunnus maccoyii(Minich et al 2020b). Its importance for the sh skin microbiota is also indirectly shown, as the genus showed decreased relative abundance in chronically stressed sh (Cámara-…”
mentioning
confidence: 62%
“…Core taxa are assumed to serve bene cial roles in the host (Sehnal et al, 2021) and the dominant taxa here, Elizabethkingia (Jacobs & Chenia, 2011) , Enterobacteriaceae, Lelliottia (Salgueiro et al, 2020), Arthrobacter (Tsoukalas et al, 2023), Deinococcus (Amill et al, 2024), Asinibacterium, Knoellia (Zou et al, 2023) are all well described from external sh microbiota. Asinibacterium and Enterobacter taxa are even considered probiotic, inhibiting pathogen growth (Halet et al, 2007;Schubiger et al, 2015).…”
Section: Estuarine Gill Core Microbiotamentioning
confidence: 99%